Sanksi Pidana terhadap Warga Negara Asing yang Melakukan Tindakan Pembobolan Anjungan Tunai Mandiri (Atm) dengan Teknik Skimming - Christin Dessy Natalia; A.A Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2020)
The level of crime vulnerability in cyberspace (cybercrime) today and its impact has exceeded the real world. Cybercrime is a dark side of technological advances that have a very broad negative impact on all areas of modern life today. The impact that will be felt as a result of the collapse of a bank is not only limited to the bank concerned but will have a broad impact on other banks. This research was conducted with the aim of uncovering the causes of the crime of burglary using skimming techniques based on Law No. 19 of 2016 and the criminal responsibility of the perpetrators of criminal acts of ATM burglary using skimming techniques based on Law no. 19 of 2016. This research employed normative legal research methods. The results of this study showed that the cause of the crime of burglary using skimming techniques is the negligence of the owner of the ATM card. In the crime of skimming ATM burglary, unawarely the victim usually has been video recorded when inserting the ATM pin and the magnetic tape has been recorded through a special device. In the results of this study, it was also stated that the crime of burglary with ATM machines using skimming techniques could be charged under Article 30 of the ITE Law, so that police officers have a legal basis to take action to investigate ATM card crimes and other electronic transactions.